Apple Watch is useful in demonstrating coffee-triggered atrial fibrillation with a very short duration: a case report. Issue 7 (28th June 2022) - Itoh, Akira
Abstract: Background: Although there are many negative reports on coffee consumption and the occurrence of atrial fibrillation (AF), several factors are involved in the metabolism of caffeine, and it is possible that the response to caffeine changes with age. We present a case in which Apple Watch was useful in detecting very brief paroxysmal AF that was thought to be triggered by coffee consumption. Case summary: The patient was a man in his early 60s. He often drank a cup of coffee after breakfast. At some point, after drinking coffee and commuting to work, he noticed palpitations. He got an Apple Watch, and when he recorded his electrocardiogram when the symptoms occurred, he found that he had AF. During the following month, the frequency of AF was examined in relation to whether coffee was consumed in the morning. Twenty days of 28 days, coffee was consumed, and of these, AF was observed on 8 days (40%). In the 8 days when he did not drink coffee, there was no AF. For the next 28 days, the coffee was changed to decaffeinated coffee and the frequency of AF was examined. AF was observed on 5 of the 24 days when decaffeinated coffee was consumed (21%). AF did not occur on the 4 days when decaffeinated coffee was not consumed. Discussion: These results may indicate that AF was significantly more common on days when coffee was consumed. In the case of frequent but short-lasting AF, it is worth considering whether coffee consumption may be a trigger.